PHOSPHONIC ACID DERIVATIVE (1981)
NEW MATERIAL:A phosphonic acid derivative of formula I (R is thienyl or substituted phenyl). EXAMPLE:1-(beta-2-Thienylalanyl)aminoethylphosphonic acid. USE:Antibacterial agent effective to gram-positive and gram-negative bacteria. PROCESS:The compound of formula I is prepared, e.g. by (1) condensing a protected amino acid of formula II (A is protecting group) or its reactive detivative with an ester of aminoethylphosphonic acid of formula III, in, e.g. a mixed solvent of dimethylformamide and dichloromethane, in the presence of a condensing agent such as dicyclohexylcarbodiimide, and (2) removing the protecting groups and at the same time hydrolyzing the reaction product.